In Vitro Susceptibility of Selected Bacteria to Three Diphosphonia Heterocyclic Compounds - Pearson, Frederick C. (1975)
The antibacterial activity of 1,1,4,4-tetraphenyl-1,4-diphosphonia-2,5-diphenylcyclohexadi-2,5-ene dichloride and two of its derivatives were screened for activity using the disk method. All derivatives exhibited antibacterial activity against gram-positive organisms tested, but little inhibition of gram-negative species was noted.